RAINFALL VARIABILITY AND EXTREME PRECIPITATION EVENTS UNDER CLIMATE CHANGE: A CASE STUDY IN PHU THO PROVINCE, VIETNAM - Ngoc Hung , Dao; My Hang, Tran; Thi Phuong, Cu; Thi Diu, Trinh; Khac Anh, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
This study investigates rainfall variability in Phu Tho province, Vietnam, focusing on total annual rainfall, the frequency of heavy rainfall days (≥ 50 mm/day),and very heavy rainfall days (≥ 100 mm/day), alongside rainy season characteristics using daily rainfall data from 1995 to 2024. Trends and variability in rainfall were analyzed using statistical methods, including the Mann–Kendall test and Sen’s slope estimator. The results indicate that trends in total annual rainfall are generally weak and spatio-temporal heterogeneity. In contrast, distinct climate change signals are evident in the intensification of rainfall and extreme weather patterns. Heavy and very heavy rainfall events contribute a disproportionately large share of total annual rainfall, particularly in mountainous terrain, despite their relatively low frequency. Furthermore, changes in rainy season duration remain limited, suggesting that recent climate impacts are primarily manifested through increased rainfall intensity rather than shifts in seasonality. These findings underscore the escalating significance of extreme rainfall events for disaster risk management and climate change adaptation in Phu Tho province.